The influence of online shopping attributes on fashion consumers’ satisfaction and loyalty: Evidence from Indonesian e-commerce - Syafrial, Ferdy (Journal of Economics and Business Letters, 2025)
This study examines how online shopping attributes shape satisfaction and loyalty among Indonesian fashion e-commerce users. Using a quantitative, descriptive–associative, cross-sectional design, we surveyed 170 consumers who had made at least one online purchase. The model specifies Information Quality, Privacy, Security, Delivery/Fulfillment, and Product Variety as antecedents; Customer Satisfaction as a mediator; Price as a moderator; and Customer Loyalty as the outcome. Measurement diagnostics indicate acceptable reliability and validity (CR > 0.87; AVE > 0.50; HTMT < 0.90). Structurally, the attributes explain substantial variance in Satisfaction (R² ≈ 0.703), while Satisfaction and Price account for moderate variance in Loyalty (R² ≈ 0.462 without moderation; ≈ 0.485 with the interaction). Delivery/Fulfillment (β ≈ 0.468, p < .001) and Product Variety (β ≈ 0.403, p < .001) significantly increase Satisfaction; Information Quality, Privacy, and Security do not. Satisfaction positively predicts Loyalty (β ≈ 0.314, p = .009). Price exerts a strong direct effect on Loyalty (β ≈ 0.456, p < .001) but does not significantly moderate the Satisfaction→Loyalty path (β ≈ 0.021, p = .263). The findings imply that logistics reliability and perceived assortment breadth are decisive levers for satisfaction in fashion e-commerce, while competitive, transparent pricing builds loyalty in parallel. Privacy and security appear to function as threshold “qualifiers”—necessary but not differentiating drivers of satisfaction in this mature platform context. Managerial priorities should emphasize SLA-backed delivery, assortment architecture, and durable value programs rather than expecting discounts to amplify the satisfaction–loyalty linkage.